2014
DOI: 10.1254/jphs.13247fp
|View full text |Cite
|
Sign up to set email alerts
|

The Cardioprotective Effect of Protocatechuic Acid on Myocardial Ischemia/Reperfusion Injury

Abstract: Abstract. Protocatechuic acid (PCA), a phenolic compound and one of the main metabolites of complex polyphenols, has been found to possess various biological activities, and it may have a potential in the treatment of ischemic heart diseases. This study explored the cardioprotective effect of PCA on myocardial ischemia/reperfusion (MI/R) injury and the underlying mechanisms. In an in vivo rat model of MI/R injury, myocardial infarct size, serum TNF-a level, and platelet aggregation were measured. In a primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…During hypoxia and reperfusion vascular endothelium is a primary site of ROS generation and target of injury. Therefore, cellular models of H/R have been widely used to evaluate the effects of drugs or active compounds (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…During hypoxia and reperfusion vascular endothelium is a primary site of ROS generation and target of injury. Therefore, cellular models of H/R have been widely used to evaluate the effects of drugs or active compounds (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…activates key components of insulin signalling pathways (Scazzocchio et al, 2015) and is protective of ischaemia/ reperfusion induced injuries of the rat heart (Tang et al, 2014) and mouse intestine (Ma et al, 2014). There is little information on the health effects of ρ-hydroxybenzoic acid other than the role of their alkyl esters, or parabens, which have been depicted as having androgen antagonist-type activity (Darbre & Harvey, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Phytosterol‐rich extracts are known to harbour antimicrobial activities. Stigmasterols and beta‐sitosterols, the main phytosterols present in T. esculentum beans, are known to harbour variable antimicrobial activities (Fukunaga et al ., ; Nejatzadeh‐Barandozi, ; Rijo et al ., ; Sanchez Perera et al ., ; Tang et al ., , ). A study by Rijo et al .…”
Section: Potential Medicinal Uses and Pharmacological Propertiesmentioning
confidence: 99%
“…Phytosterol-rich extracts are known to harbour antimicrobial activities. Stigmasterols and beta-sitosterols, the main phytosterols present in T. esculentum beans, are known to harbour variable antimicrobial activities (Fukunaga et al, 1989;Nejatzadeh-Barandozi, 2013;Rijo et al, 2009;Sanchez Perera et al, 2007;Tang et al, 2014aTang et al, , 2014b. A study by Rijo et al (2009) demonstrated low antimicrobial activity of stigmasterol against S. aureus (62 μg/mL) compared with that for vancomycin (1.95 μg/mL).…”
Section: Action Against Gastroenteritismentioning
confidence: 99%
See 1 more Smart Citation